2022
DOI: 10.3233/jpd-212877
|View full text |Cite
|
Sign up to set email alerts
|

The Compound ATH434 Prevents Alpha-Synuclein Toxicity in a Murine Model of Multiple System Atrophy

Abstract: Background: An elevation in iron levels, together with an accumulation of α-synuclein within the oligodendrocytes, are features of the rare atypical parkinsonian disorder, Multiple System Atrophy (MSA). We have previously tested the novel compound ATH434 (formally called PBT434) in preclinical models of Parkinson’s disease and shown that it is brain-penetrant, reduces iron accumulation and iron mediated redox activity, provides neuroprotection, inhibits alpha synuclein aggregation and lowers the tissue levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…We recently showed that clearance of p-Ser129 α-synuclein alleviates cognitive and motor dysfunction in a Parkinson’s disease mouse model [ 50 ]. We also developed a therapeutic compound targeting metal ions, which has the potential to modulate α-synuclein metal binding and alleviate its accumulation [ 122 , 123 ]. Based on our finding that fatty-acid-binding proteins are critical for the accumulation of α-synuclein following phosphorylation [ 17 , 19 , 37 ], we intend to develop more fundamental therapeutics and diagnostic tools for α-synucleinopathies, including Parkinson’s disease, DLB, and multiple system atrophies.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that clearance of p-Ser129 α-synuclein alleviates cognitive and motor dysfunction in a Parkinson’s disease mouse model [ 50 ]. We also developed a therapeutic compound targeting metal ions, which has the potential to modulate α-synuclein metal binding and alleviate its accumulation [ 122 , 123 ]. Based on our finding that fatty-acid-binding proteins are critical for the accumulation of α-synuclein following phosphorylation [ 17 , 19 , 37 ], we intend to develop more fundamental therapeutics and diagnostic tools for α-synucleinopathies, including Parkinson’s disease, DLB, and multiple system atrophies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent reports of the efficacy of a quinazolinone derivative, PBT434, in a Phase I trial involving Multiple System Atrophy indicate the potential of such chemical platforms ( 199 ). PBT434 suppresses α-synuclein toxicity in models of Parkinson's disease ( 200 ) and MSA ( 201 ). PBT434 has a moderate affinity for both ferrous and ferric iron (stability constants ~10 7 ); has a redox potential that supports cell anti-oxidant activity; and exhibits facile equilibration across the BBB without disrupting iron homeostasis in BMVEC ( 200 , 202 ).…”
Section: Therapeutic Interventions For Inflammation-induced Brain Iro...mentioning
confidence: 99%
“…The compound decreased α-syn aggregation, toxicity and activated DA receptors D2/D3 in animal models of PD [ 297 ]. PBT434 is a 8-hydroxyquinoline (8-HQ) derivative, which, apart from binding iron, was shown to decrease levels of oligomeric and fibrillar α-syn in murine models of MSA and PD [ 298 , 299 , 300 ]. The efficacy and safety of PBT434 were investigated in a phase I trial, in which the compound achieved a favorable and proportional pharmacokinetic profile, was non-toxic and well-tolerated [ 301 ].…”
Section: Drugs Targeting α-Synucleinmentioning
confidence: 99%